2014
DOI: 10.1002/cncr.29162
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of patient navigation to increase adherence with screening colonoscopy among minority individuals

Abstract: Background Colorectal cancer (CRC) screening is underutilized by minority populations. Patient navigation increases adherence with screening colonoscopy. We estimated the cost-effectiveness of navigation for screening colonoscopy from the perspective of a payer seeking to improve population health. Methods We informed our validated model of CRC screening with inputs from navigation studies in New York City (population 43% African American, 49% Hispanic, 4% White, 4% Other; base case screening 40% without and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Three years into the first 6-year cycle of the program, a hypothetical 5% and 10% increase in compliance would have resulted in a screening promotion cost per person of under $100 and $50 respectively. Studies have shown that evidence-based promotion activities can increase screening utilization (Ladabaum, Mannalithara, Jandorf, & Itzkowitz, 2015; Pinkowish, 2009; Sabatino et al, 2012; Wilson, Villarreal, Stimpson, & Pagan, 2015) but the design of the CRCCP promotion interventions did not allow for program impacts to be assessed independent of overall state population level impacts. The findings from this study can therefore assist policy makers to assess the potential cost and benefit of the program and provide effectiveness thresholds to guide future program funding decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Three years into the first 6-year cycle of the program, a hypothetical 5% and 10% increase in compliance would have resulted in a screening promotion cost per person of under $100 and $50 respectively. Studies have shown that evidence-based promotion activities can increase screening utilization (Ladabaum, Mannalithara, Jandorf, & Itzkowitz, 2015; Pinkowish, 2009; Sabatino et al, 2012; Wilson, Villarreal, Stimpson, & Pagan, 2015) but the design of the CRCCP promotion interventions did not allow for program impacts to be assessed independent of overall state population level impacts. The findings from this study can therefore assist policy makers to assess the potential cost and benefit of the program and provide effectiveness thresholds to guide future program funding decisions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a stakeholder hospital, C5 participants demonstrated that lay individuals (those older than 50 years who have undergone colonoscopy) can be readily trained to serve effectively as peer patient navigators . Modeling studies have demonstrated that navigating primarily African American and Latino populations of low socioeconomic status from this same hospital is cost‐effective . This demonstration led to the development of additional training materials (including a focus on cultural issues) and a manual.…”
Section: Initiatives To Achieve Goalsmentioning
confidence: 99%
“…21 Modeling studies have demonstrated that navigating primarily African American and Latino populations of low socioeconomic status from this same hospital is cost-effective. 22 This demonstration led to the development of additional training materials (including a focus on cultural issues) and a manual. The navigator program has been a consistent focus of C5, and ongoing evaluation and updates on the use and value of navigation have encouraged robust support of the program.…”
Section: Dohmh Detailing Initiativementioning
confidence: 99%
“…However, despite the success of PN services in improving both CRC screening and the quality of screening, the current payment models do not cover PN services . Furthermore, very few studies to date have reported the resource requirements and cost effectiveness of PN interventions . To develop the business case and determine appropriate payment models for PN services, we need cost and cost‐effectiveness studies on a broad spectrum of PN interventions applied across varied patient cohorts and health care settings.…”
Section: Introductionmentioning
confidence: 99%